The effectiveness of smoking cessation interventions for socio-economically disadvantaged women: a systematic review and meta-analysis - Hayes, Catherine (My University, 2022)
Introduction: This systematic review and meta-analysis assessed the effectiveness of smoking cessation interventions among women smokers in low socio-economic status (SES) groups or women living in disadvantaged areas who are historically underserved by smoking cessation services. Methods: A systematic literature search was conducted using MEDLINE (OVID), EMBASE, Cochrane, CINAHL, PsychINFO and Web of Science databases. Eligibility criteria included randomised controlled trials of any smoking cessation intervention among women in low SES groups or living in socio-economically disadvantaged areas. A random effects meta-analysis assessed effectiveness of interventions on smoking cessation. Risk of bias was assessed with the Cochrane Risk of Bias tool. The GRADE approach established certainty of evidence. Results: A total of 396 studies were screened for eligibility and 11 (6153 female participants) were included. Seven studies targeted women-only. 5/11 tested a form of face-to-face support. A pooled effect size was estimated in 10/11 studies. At end of treatment, two-thirds more low SES women who received a smoking cessation intervention were more likely to stop smoking than women in control groups (risk ratio (RR) 1.68, 95% CI 1.36-2.08, I2= 34%). The effect was reduced but remained significant when longest available follow-up periods were pooled (RR 1.23, 95% CI 1.04-1.48, I2 = 0%). There was moderate-to-high risk of bias in most studies. Certainty of evidence was low. Conclusions: Behavioural and behavioural + pharmacotherapy interventions for smoking cessation targeting women in low SES groups or women living in areas of disadvantage were effective in the short term. However, longer follow-up periods indicated reduced effectiveness. Future studies to explore ways to prevent smoking relapse in this population are needed. Systematic review registration: PROSPERO: CRD42019130160.
PUBLISHED
Keywords: Behavioural; Cessation; Gender; Health disparities; Meta-analysis; Tobacco control; Cancer; Inclusive Society; Health; Social exclusion